why not just take the √ of both sides as it stands
(x-2)^2 = 49
x-2 = ± 7
x = 2 ± 7
= 9 or -5
you had x^2 - 4x - 45 = 0
which would have factored to
(x-9)(x+5) = 0
x = 0 or x = -5
If (x - 2)^2 = 49, then x could be
(A) -9
(B) -7
(C) 2
(D) 5
(E) 9
(x - 2)^2 = 49
(x - 2) (x - 2) = 49
x^2 - 2x - 2x + 4 = 49
x^2 - 4x + 4 - 4 = 49 - 4
x^2 - 4x = 45
I am not sure what to do from here.
2 answers
I'm sorry I figured out what I did wrong.
(x - 2)^2 = 49
(x - 2) (x - 2) = 49
x^2 - 2x - 2x + 4 = 49
x^2 - 4x + 4 = 49
x^2 - 4x + 4 - 49 = 49 - 49
x^2 - 4x - 45 = 0
(x + 5) (x - 9) = 0
Solution is {-5} , {9}, Answer choice E
(x - 2)^2 = 49
(x - 2) (x - 2) = 49
x^2 - 2x - 2x + 4 = 49
x^2 - 4x + 4 = 49
x^2 - 4x + 4 - 49 = 49 - 49
x^2 - 4x - 45 = 0
(x + 5) (x - 9) = 0
Solution is {-5} , {9}, Answer choice E